The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.bbalip.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as regulators of endothelial cell functions in cardiometabolic diseases

Abstract: Endothelial cells (ECs) provide nutrients and oxygen essential for tissue homeostasis. Metabolic imbalances and other environmental stimuli, like cytokines or low shear stress, trigger endothelial inflammation, increase permeability, compromise vascular tone, promote cell proliferation and ultimately cause cell death. These factors contribute to EC dysfunction, which is crucial in the development of cardiometabolic diseases. microRNAs (miRNAs) are small non-coding RNAs that have important functions in the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 117 publications
0
28
0
Order By: Relevance
“…Increasing evidence suggests that miRNAs play a significant role in the diagnosis of T2DM or as therapeutic targets 48 50 and may also regulate endothelial cell function and angiogenesis 51 , 52 . In this study, we found significant differences in the serum miRNA expression profiles of Han Chinese T2DM patients with or without CLI.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that miRNAs play a significant role in the diagnosis of T2DM or as therapeutic targets 48 50 and may also regulate endothelial cell function and angiogenesis 51 , 52 . In this study, we found significant differences in the serum miRNA expression profiles of Han Chinese T2DM patients with or without CLI.…”
Section: Discussionmentioning
confidence: 99%
“…These undesired effects explain why diminished Nitric Oxide secretion in regions with disturbed flow, such as arterial branch points, are prone to develop atheromas [110]. Additionally, hemodynamics itself has a profound effect on miRNA expression, and differentially regulated miRNAs contribute to the regulation of shear stress-mediated transcriptional programs [95,111]. Several reports showed that shear stress induced the expression of miR-21 with contrasting effects.…”
Section: Regulation Of Vascular Tonementioning
confidence: 99%
“…On the other hand, endothelial dysfunction is fundamentally responsible for prothrombotic and proinflammatory state of the vasculature [9, 10]. Inflammation disrupts normal functionality of the endothelial cells, contributing to the development and progression of cardiometabolic diseases [11]. Prevention of excessive endothelial inflammation may provide promising approaches for treatment of inflammation-related cardiovascular diseases [12].…”
Section: Introductionmentioning
confidence: 99%